Relativistic hydrodynamical simulations of the effects of the stellar wind and the orbit on high-mass microquasar jets. Issue 3 (15th December 2021) - Barkov, Maxim V; Bosch-Ramon, V
ABSTRACT: High-mass microquasar jets, produced in an accreting compact object in orbit around a massive star, must cross a region filled with stellar wind. The combined effects of the wind and orbital motion can strongly affect the jet properties on binary scales and beyond. The study of such effects can shed light on how high-mass microquasar jets propagate and terminate in the interstellar medium. We study for the first time, using relativistic hydrodynamical simulations, the combined impact of the stellar wind and orbital motion on the properties of high-mass microquasar jets on binary scales and beyond. We have performed 3-dimensional relativistic hydrodynamic simulations, using the PLUTO code, of a microquasar scenario in which a strong weakly relativistic wind from a star interacts with a relativistic jet under the effect of the binary orbital motion. The parameters of the orbit are chosen such that the results can provide insight on the jet-wind interaction in compact systems like for instance Cyg X-1 or Cyg X-3. The wind and jet momentum rates are set to values that may be realistic for these sources and lead to moderate jet bending, which together with the close orbit and jet instabilities could trigger significant jet precession and disruption. For high-mass microquasars with orbit size a ∼ 0.1 AU, and (relativistic) jet power L_j10^37(M_w/10^-6 M_yr^-1) erg s −1, where M_w is the stellar wind mass rate, the combined effects of the stellar wind and orbital motion can induce relativistic jet disruption on scales ∼1 AU.